Penerapan Produksi Bersih Produk Perikanan Pada Pengolahan Kerupuk Ikan Di Desa Parit Baru Kecamatan Selakau Kabupaten Sambas - Nurhaban Nurhaban; Ifa Auliandini; Indah Indah; Risma Wati (Journal of Fisheries and Marine Applied Science, 2025)
Abstract. Clean production is a preventive approach in environmental management that aims to minimize waste and improve resource efficiency without sacrificing product quality. This study aims to evaluate the application of the principle of clean production in a household-scale fish cracker processing business unit in Parit Baru Village, Selakau District, Sambas Regency. The research uses a qualitative descriptive method with data collection techniques through direct observation, in-depth interviews, and visual documentation. The results showed that organoleptically the fish crackers produced had good quality with a uniform color appearance, a non-pungent aroma, and a crispy and chewy texture. However, from the results of the assessment using the CPPOB-IRT form, 26 discrepancies were found divided into minor, major, serious, and critical categories, especially in the aspects of sanitation, employee hygiene, building conditions, and production documentation. Narrow production space, non-one-way process flows, and lack of sanitation facilities are the main challenges. There is no raw material recording available and there is no defective product recall procedure. The results of the study show that the application of the principle of clean production and strengthening the quality system is still very necessary. With simple intervention and continuous assistance from related agencies, the product quality and competitiveness of the fish cracker household industry have the potential to be significantly improved. Keywords: journal, template, abstract, writing, paper. Keywords: Fish crackers, product quality, Net production, sanitation, UMKM.